Análise dos riscos físicos e ergonômicos em roçadora transversal motorizada - Poletto Filho, José Antonio; Santos, João Eduardo Guarnetti dos [UNESP]; Poletto, Heliana Maria Cassetari (My University, 2015)
According to Statistical Yearbook of Social Security (2011), the number of accidents at work recorded in the agricultural sector is quite high, in the year 2010 there are records of thirty-four thousand nine hundred and ninetysix accidents, and in the year of 2011 there were thirty-one thousand and ninety-six accidents in the industry. Among so many diseases and accidents at work hearing loss is one of them. According to the Pan American Health Organization (2011) the Occupational hearing loss is then jury to the worker's health, often in the workplace. Mechanical vibrations are also present in many human activities exposing employees to an extremely aggressive agent. The combined action of these two factors can cause damage to the health of the worker, in this way, noise and vibration are the two major occupational agents present in the brush cutter operator activity. In the case there is another risk factor, the open work, which exposes the employee to the Sun’s rays and the high temperature indices. Studies have shown that: noise exceeds 115 dB (A) vibration 4.0 m/s2 and thermal stress of 29.9 o C. Ergonomic evaluations also demonstrated that the activity cause injury to workers.

De acordo com Anuário Estatístico da Previdência Social (2011), o número de acidentes no trabalho registrados no setor Agropecuário é bastante elevado, no ano de 2010 há registros de trinta e quatro mil novecentos e noventa e seis acidentes, e no ano de 2011 houve trinta e um mil e noventa e seis acidentes no setor. Dentre tantas doenças e acidentes no trabalho a perda auditiva é uma delas. Segundo a Organização Pan-Americana de Saúde (2011) a Perda Auditiva Ocupacional (PAO) é o agravo à saúde do trabalhador, frequente no ambiente de trabalho. Vibrações mecânicas também estão presentes em muitas atividades humanas expondo os colaboradores a um agente extremamente agressivo. A ação combinada destes dois fatores pode causar danos à saúde do trabalhador, desta forma, o ruído e a vibração são os dois grandes agentes ocupacionais presentes na atividade do operador de roçadora. Neste caso há ainda outro fator de risco, o trabalho a céu aberto, que expõe o trabalhador a raios solares e a índices de temperatura elevados. Os estudos demonstraram que: ruído ultrapassa 115 dB(A), vibração 4,0 m/s2 e estresse térmico de 29,9 0 C. As avaliações ergonômicas também demonstraram que a atividade causa lesão aos trabalhadores.
Keywords: Thermal stress; Mechanical vibrations; Agricultural sector; Estresse térmico; Vibrações mecânicas; Setor Agropecuário